SIMPLIFIED MATHEMATICAL MODEL OF FINANCIAL CRISIS - KROUGLOV, Alexei (Journal of Advanced Studies in Finance, 2013)
The framework of mathematical dynamics of economic systems is applied to the development of financial crisis. A view is proposed that the severity of financial crises can be explained by means of superposition of the fluctuations on connected markets exhibited in the form of a resonance phenomenon. The practical actions of the central banks are criticized as contradicting to theoretical implications of the model.